2015
DOI: 10.1161/circresaha.116.304794
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Non-Growth Factor Role for GM-CSF in Advanced Atherosclerosis

Abstract: Rationale Granulocyte macrophage colony stimulating factor (GM-CSF, Csf2) is a growth factor for myeloid-lineage cells that has been implicated in the pathogenesis of atherosclerosis and other chronic inflammatory diseases. However, the role of GM-CSF in advanced atherosclerotic plaque progression—the process that gives rise to clinically dangerous plaques—is unknown. Objective To understand the role of GM-CSF in advanced atherosclerotic plaque progression. Methods and Results Ldlr−/− mice and Csf2−/−Ldlr−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 65 publications
2
39
1
1
Order By: Relevance
“…In vitro stimulation of PBMCs gives the opportunity to study the interplay between different immune cells and 24,25 Recently, however, IL-23 has also been shown to have important proatherogenic effects on macrophages, independently of IL-17. 26 In our study, IL-23 significantly increased TNF release in patient monocytes, and we also found colocalization of IL-23/IL-23R and macrophages within the atherosclerotic lesion, supporting an interplay between monocytes/macrophages and IL-23 in atherosclerotic disease. In contrast to the increased expression of IL-23/IL-23R in carotid plaques, this was not seen in PBMCs from these patients, suggesting that the upregulation of IL-23/IL-23R in PBMC-related cells, such as macrophages, within the atherosclerotic lesion reflects processes within the plaque.…”
Section: Discussionsupporting
confidence: 82%
“…In vitro stimulation of PBMCs gives the opportunity to study the interplay between different immune cells and 24,25 Recently, however, IL-23 has also been shown to have important proatherogenic effects on macrophages, independently of IL-17. 26 In our study, IL-23 significantly increased TNF release in patient monocytes, and we also found colocalization of IL-23/IL-23R and macrophages within the atherosclerotic lesion, supporting an interplay between monocytes/macrophages and IL-23 in atherosclerotic disease. In contrast to the increased expression of IL-23/IL-23R in carotid plaques, this was not seen in PBMCs from these patients, suggesting that the upregulation of IL-23/IL-23R in PBMC-related cells, such as macrophages, within the atherosclerotic lesion reflects processes within the plaque.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study has demonstrated that GM-CSF functions as a growth factor and increases macrophage apoptosis in advanced lesions. 22 These effects are mediated by IL-23, another cytokine that we detected after TLR7 activation. Several prominent pro-inflammatory cytokines were unaffected by the TLR7 ligand in the plaques, including IFNc and IL-6.…”
Section: Discussionmentioning
confidence: 77%
“…68 On the one hand, there is evidence that increased apoptosis of macrophages in advanced lesions, in which the clearance of apoptotic cells is impaired, 69 leads to enhanced lesion progression, expansion of the necrotic core, and increased risk of plaque rupture. Under these conditions, macrophage apoptosis can be enhanced by, for example, elevated endoplasmic reticulum stress, 70 granulocyte macrophage colony-stimulating factor-induced IL-23 production, 71 or excessive accumulation of oxysterols. 72 Especially relevant for the present study, PLCβ3 deletion results in a reduction in atherosclerotic lesions with increased macrophage apoptosis and reduced Bcl-XL expression.…”
Section: Discussionmentioning
confidence: 99%